THE USE OF BILINGUAL STORIES TO IMPROVE THE STUDENT’S MASTERY OF ENGLISH VOCABULARY: A CASE OF THE EIGHT GRADE STUDENTS OF SMP N 2 GROBOGAN - Ernawati Ernawati (Universitas PGRI Semarang, 2013)
The main objectives of this research are: 1) To find out the eight grade students’ of SMP N 2 Grobogan in vocabulary mastery before and after they are taught using bilingual stories. 2) To find out whether or not there is a significant difference of the vocabulary mastery of the eight grade students of SMP N 2 Grobogan in Academic Year 2012/2013 before and after being taught by bilingual stories. The study is an experimental research. The population of the research is the Eight grade students of SMP N 2 Grobogan 2012/2013. The writer takes 33 students in VIII G as a Experiment class and 34 students in VIII F as a Control class. The result of this study show that the students in the experiment group have little better development in the average scores than the control group in bilingual test. The difference of the development of the average scores is statistically significant at the (0.05) alpha level of significance. The research finds that there is no significant difference for those who taught with bilingual story and those without bilingual story. The difference is shown by the development of the average scores. The group that use bilingual story got little better in the average scores (72.5) than those without bilingual story (72.2). The use of bilingual story could not give more significant difference in improving students’ mastery of vocabulary. So the writer concludes that the bilingual story can not help students in improving the mastery of vocabulary the 8th Year Students of SMP N 2 Grobogan. A conclusion, this research shows that the students taught using bilingual story and students using bilingual story can’t show the significant difference. So, using bilingual story can’t improve the students’ mastery of vocabulary in SMP N 2 Grobogan.